Fieldwork - Pole, Christopher J. (Christopher John), 1959- (London : SAGE Publications, 2005)
v. 1. Origins and definitions of fieldwork -- v. 2. The fieldwork experience: methods and methodology -- v. 3. Ethics and politics in fieldwork -- v. 4. Analysis, outcomes, and reflections